2020
DOI: 10.1161/jaha.119.013227
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Cardiopathy in the Absence of Atrial Fibrillation Increases Risk of Ischemic Stroke, Incident Atrial Fibrillation, and Mortality and Improves Stroke Risk Prediction

Abstract: Background Atrial fibrillation ( AF ) is a major, often undetected, cardiac cause of stroke. Markers of atrial cardiopathy, including left atrial enlargement ( LAE ) or excessive atrial ectopy ( EAE ) increase the risk of AF and have shown associations with stroke. We sought to determine whether these markers improve stroke risk prediction beyond traditional vascular risk factors (eg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 54 publications
1
21
0
Order By: Relevance
“…The concept of atrial cardiopathy has been proposed as a potential cause of AF, and it can lead to thromboembolism due to left atrial function abnormality, even without AF [ 27 ]. Data from a large retrospective cohort from Canada indicated that, in the absence of AF, increased LAD significantly and independently increased the risk of ischemic stroke at 2 years with C-statistics ranging from 0.68 to 0.75 [ 28 ]. The combination of LAD and CHA 2 DS 2 -VASc score, even in patients without AF, significantly improved stroke risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of atrial cardiopathy has been proposed as a potential cause of AF, and it can lead to thromboembolism due to left atrial function abnormality, even without AF [ 27 ]. Data from a large retrospective cohort from Canada indicated that, in the absence of AF, increased LAD significantly and independently increased the risk of ischemic stroke at 2 years with C-statistics ranging from 0.68 to 0.75 [ 28 ]. The combination of LAD and CHA 2 DS 2 -VASc score, even in patients without AF, significantly improved stroke risk prediction.…”
Section: Discussionmentioning
confidence: 99%
“…Left atrial cardiopathy is the process of structural and electrical remodeling preceding clinically manifest AF. Markers of left atrial cardiopathy including increased P-wave terminal in lead V 1 , left atrial enlargement, and excessive atrial ectopy increase the risk of AF and have recently been identified as a direct risk factor for stroke in the absence of AF [60]. Further, preliminary studies have shown that left atrial cardiomyopathy may also increase the risk of cognitive decline [61], suggesting that detection of atrial cardiopathy might represent an important opportunity to improve the estimation of dementia risk in aging adults.…”
Section: Does the Heart Matter For Your White Matter? Novel Cardiac Markers Of Dementia Riskmentioning
confidence: 99%
“…heart failure, cognitive impairment, atrial cardiopathy, dementia, atrial fibrillation 2020; Edwards et al, 2020). While the link between AF and HF and cognition is clear, data on AC and cognition are scarce (Aldrugh et al, 2017;Rosler and Schnabel, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Potential biomarkers of AC include imaging, electrophysiological, and serum abnormalities. AC may also be a substrate for multiple primary cardiac disorders, including atrial fibrillation (AF) and heart failure (HF), and has been linked to increased risk for stroke and higher stroke mortality ( Ahmad et al, 2020 ; Edwards et al, 2020 ). While the link between AF and HF and cognition is clear, data on AC and cognition are scarce ( Aldrugh et al, 2017 ; Rosler and Schnabel, 2020 ).…”
Section: Introductionmentioning
confidence: 99%